A systematic review of photovoice as participatory action research strategies - Nadi Suprapto; Titin Sunarti; Suliyanah Suliyanah; Desi Wulandari; Hasan Nuurul Hidayaatullaah; Alif Syaiful Adam; Husni Mubarok (Institute of Advanced Engineering and Science, 2020)
Photovoice research is conducted by researchers to communicate images or photographs, and it has high confidence in analyzing the value, story or meaning of an image. Several previous studies that examined photovoice as a research strategy were analyzed and reviewed. This systematic review used an article selection process. It was defining the purpose, conducting a literature search, pulling articles by reading abstracts, reading the full paper, data abstraction, and conducting an analysis. The photovoice article selection was classified into education, health, and social science domain. Finally, forty-one articles have been reviewed with the total of participants involved ranged from five to fifty individuals. The majority of research method in the articles was participatory action research (PAR) through qualitative inquiry or field visits. Meanwhile, the research instruments used photography, documentation, observation, and interviews. In various fields of research, photovoice is able to increase the understanding of individuals or groups to interpret the content of an image or photo.